2015
DOI: 10.1021/acsami.5b04217
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zeolitic Imidazolate Framework Core–Shell Nanosheets Using Zinc-Imidazole Pseudopolymorphs

Abstract: Zeolitic imidazolate frameworks (ZIFs) are an emerging class of microporous materials that possess an organic flexible scaffold and zeolite-like topology. The catalytic and molecular-separation capabilities of these materials have attracted considerable attention; however, crystal-shape engineering in ZIF materials remains in its infancy. This is the first study to report an effective method for tailoring the near-spherical crystal morphology of ZIF-8 using its leaf-like pseudopolymorph, ZIF-L. A thin, uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 64 publications
0
17
0
3
Order By: Relevance
“…In contrast, the solution zinc : 2mIM ratio remains 1 : 8, leading to ZIF-L crystal growth. It has been previously reported that when separately synthesized ZIF-8 and ZIF-L crystals are combined into a single solution, they will coalesce into a new core–shell composite 40. The addition of ox-SWCNTs into low zinc : 2mIM ratio solutions produces similar ZIF-L/ZIF-8/ox-SWCNT composites in a one-pot synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the solution zinc : 2mIM ratio remains 1 : 8, leading to ZIF-L crystal growth. It has been previously reported that when separately synthesized ZIF-8 and ZIF-L crystals are combined into a single solution, they will coalesce into a new core–shell composite 40. The addition of ox-SWCNTs into low zinc : 2mIM ratio solutions produces similar ZIF-L/ZIF-8/ox-SWCNT composites in a one-pot synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…MOF-based heterogeneous structures including core-shell structure 44,45 and layer-by-layer structure 41,46 have previously been prepared, and the MOF composites thus-formed show improved separation performance as a result of the engineered pore structure. Specic MOFs can be selected as an interlayer for the growth of target MOFs in terms of the difference in microstructures and chemical characteristics.…”
Section: Surface Characteristicsmentioning
confidence: 99%
“…On the other hand, adjusting external synthetic conditions appropriately, such as temperature, guest adsorption or evacuation, and mechanical pressure could also induce structural transformations of ZIFs, forming new thermodynamically or kinetically stable topotactic phases . Although most studies of ZIFs are focused on the specific morphologies/phases and their correlative properties, carefully understanding topotactic phase transformations, with corresponding morphology evolution, is essential for achieving precise morphology‐controlling strategies and further excellent tunable properties …”
Section: Introductionmentioning
confidence: 99%
“…[13,14] For example, through as olution-mediatedp rocess, ZIFs with differentm orphologies, such as hexagonal nanoparticles, [15] rhombic dodecahedrons, [16] leaf-shaped plates, [17] and cubes [18] were obtained by use of poly(diallyldimethylammonium chloride), cetyltrimethylammonium bromide surfactant, controlo f2 -methylimidazole (2-MIM) concentration, and pH value, respectively.O nt he other hand, adjustinge xternal synthetic conditions appropriately,s uch as temperature, [13] guest adsorption or evacuation, [11,12] and mechanical pressure [19] could also induce structuralt ransformations of ZIFs, forming new thermodynamically or kinetically stable topotactic phases. [20] Although most studies of ZIFs are focused on the specific morphologies/phases andt heir correlativep roperties, [21,22] carefullyu nderstandingt opotactic phase transformations, withc orresponding morphologye volution, is essential for achieving precise morphology-controlling strategies and furtherexcellent tunable properties. [17,18,21,23] IsostructuralZIF-8 and ZIF-67, with sodalite topology,are frequently studied 3D frameworks, and are made up by linking Zn (ZIF-8) or Co (ZIF-67) metal ions with 2-methylimidazole (2-MIM).…”
Section: Introductionmentioning
confidence: 99%